2014
DOI: 10.1007/s10072-014-1980-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated concentration of C-reactive protein is associated with pregnancy-related co-morbidities but not with relapse activity in multiple sclerosis

Abstract: During pregnancy, alterations take place in mother's immune system with the goal of maintaining a successful pregnancy, and delivering healthy offspring. Immune alterations include activation of the innate immune system and dampening of cell-mediated adaptive immunity. Due to these alterations, cell-mediated autoimmune diseases typically ameliorate during pregnancy. The objectives of this study were to evaluate whether C-reactive protein (CRP) concentration, a sensitive marker of systemic inflammation (1) is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The modified Kupperman Menopausal Index Ates et al 2022 [58] Matched pair study (POI, N = 62; Control, N = 62) Fatigue did not differ significantly between the groups Fatigue Severity Scale Premature Ovarian Failure Stege et al 2008 [59] Case-control study (POF, N = 81; Control, N = 68) Fatigue did not differ significantly between the groups The Shortened Fatigue Questionnaire higher CRP, an indicator of systemic inflammation, may be somewhat predictive of pregnancy-related comorbidities [68]. A small single-center retrospective study revealed that more patients with MS underwent elective cesarean deliveries due to fatigue [69].…”
Section: Chalder Fatigue Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The modified Kupperman Menopausal Index Ates et al 2022 [58] Matched pair study (POI, N = 62; Control, N = 62) Fatigue did not differ significantly between the groups Fatigue Severity Scale Premature Ovarian Failure Stege et al 2008 [59] Case-control study (POF, N = 81; Control, N = 68) Fatigue did not differ significantly between the groups The Shortened Fatigue Questionnaire higher CRP, an indicator of systemic inflammation, may be somewhat predictive of pregnancy-related comorbidities [68]. A small single-center retrospective study revealed that more patients with MS underwent elective cesarean deliveries due to fatigue [69].…”
Section: Chalder Fatigue Scalementioning
confidence: 99%
“…These dysregulations involve cell-mediated immunity, including impairment of the function of NK cells, hypo-reactivity of T cells to the antigen, the activation of monocyte macrophages, and the persistence of autoreactive cells [116]. Concurrently, they manifest as changes in many inflammation-related markers, such as increased CRP levels [68], elevation in pro-inflammatory factors like interleukin-1β, interleukin-6, interleukin-12, interleukin-2, tumor necrosis factor-alpha and interferon-gamma, increased expression of nuclear factor kappa-B, as well as decreased levels of anti-inflammatory factors like interleukin-8, interleukin-13, interleukin-15, and interleukin-23 [117]. The changes in inflammationrelated profile support that patients experiencing fatigue are in a low-grade inflammatory state.…”
Section: Low-grade Inflammatory Activationmentioning
confidence: 99%